Intuitive Politicians or Unintuitive Penitents? Regret Aversion, Accountability and Justification in the Decoy Effect - Connolly, Terry (Institutional Knowledge at Singapore Management University, 2011)
Several studies have shown that the decoy (or attraction) effect is amplified when participants anticipate having to justify their choices to an external audience. We report here two experiments examining the impact on the decoy effect of making future regret possibilities salient, a manipulation that has been shown in several earlier studies to generate pressure to examine and improve one's decision process. Experiment 1 showed that making regret salient eliminated the decoy effect in a personal preference task. Experiment 2 replicated this finding for a different personal preference task and for a prediction task. It also replicated previous findings that external accountability demands exacerbated the decoy effect. We interpret both effects in terms of justification demands, but to different audiences. Seeking justification to others (responding to accountability demands) exacerbated the decoy effect; seeking justification to oneself (responding to regret salience) eliminated it. The earlier 'intuitive politician' metaphor describes responses to demands for external justification. We propose here an alternative, the 'intuitive penitent', driven by thoughts of possible later regret to justify her choices to herself. These justification ideas both contribute to a theoretical account of the decoy effect and offer an effective debiasing procedure for it.